Creep of mafic dykes infiltrated by melt in the lower continental crust (Seiland Igneous Province, Norway) - Degli Alessandrini, G; Menegon, L; Malaspina, N; Dijkstra, A; Anderson, M. (Lithos, 2017)
A dry mafic dyke from a continental lower-crustal shear zone in the Seiland Igneous Province (northern Norway) experienced syn-kinematic melt-rock interaction. Viscous shearing occurred at T ≈ 800 °C, P ≈ 0.75–0.95 GPa and was coeval with infiltration of felsic melt from adjacent migmatitic metapelites. The dyke has a mylonitic microstructure where porphyroclasts of orthopyroxene, clinopyroxene and plagioclase are wrapped by a fine-grained (4–7 μm) polyphase mixture of clinopyroxene + orthopyroxene + plagioclase + quartz + ilmenite ± K-feldspar ± apatite. Microstructural observations and electron backscatter diffraction analysis indicate that the porphyroclasts deformed by a combination of dislocation glide and fracturing, with only a limited record of dislocation creep, recovery and dynamic recrystallization. We identified diffusion creep as the dominant deformation mechanism in the mixture based on the small grain size, phase mixing and weak crystallographic preferred orientation of all phases (interpreted as the result of oriented grain growth during viscous flow). The polyphase mixture did not form by dynamic recrystallization or by mechanical fragmentation of the porphyroclasts, but rather by melt-rock interaction. Thermodynamic models indicate that the syn-kinematic mineral assemblage results from the chemical interaction between a pristine mafic dyke and ca. 10 vol.% of felsic melt infiltrating from the adjacent partially molten metapelites. Extrapolation of laboratory-derived flow laws to natural conditions indicates that the formation of interconnected layers of fine-grained reaction products deforming by diffusion creep induces a dramatic weakening in the mafic granulites, with strain rates increasing up to 2–3 orders of magnitude. The reaction weakening effect is more efficient than the weakening associated with melt-assisted diffusion creep in the presence of up to 10 vol.% of infiltrated melt without formation of fine-grained reaction products. Thus, we conclude that weakening by dramatic grain-size ...